The Management Project as a Model of Educational Leadership - Iorio Fontana, Cristelle; Sánchez-Huete, Juan Carlos (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
Several research studies highlight that school management is one of the main factors that will determine the efficiency of the educational institution in the programs developed. a pivotal element of this effective leadership is crystallized in the leadership proj ect, which is developed during the tenure. We illustrate this with a specific example: the IberIa Primary School, in las Palmas de Gran Canaria. The approach of the objectives presented are based on the results from previous academic years, which have assisted to understand the strengthens and weaknesses of the school center. This entails proposing new initiatives regarding weaknesses and enriching strengths based on the opti mization of achievements. It is undoubtedly an example of the transformative power of education: as educators, we must become aware of the great responsibility that society entrusts us with, as we are indispensable agents in this process of change.